Pengembangan Aplikasi Penulisan Aksara Jawa Berbasis Desktop - Kamil, Ilham Insan; , Bana Handaga,S.T.,M.T.,Ph.D (2016)
Aksara Jawa or Javanese script is an alphabet used by Javanese to write Javanese language. Yes, it is not easy to write Javanese script in computer media. This is attested by the very minimum software application which can support writing and displaying the Javanese script. Replenishment of the Javanese script into Unicode Standard in version 5.2 provides more opportunities for software developers to expand the utilization of the Javanese script in a variety needs, including development of the Javanese script font. Development of this application described on this paper. And it has ability to write, view, also print the document which contain Javanese script. It is a windows form-base application, and it was built using Microsoft Visual Studio 2015. This application is expected to facilitate the computer users in writing Javanese script on computer media as well as to preserve and introduce Javanese cultures in the whole societies. The application testing performed in two ways, Black Box Testing and test to a local community. The test result showed that this application is running properly with no error, match to use case, easy to use, and attract more people to learn more about Javanese Script.